2022
DOI: 10.1186/s12889-022-14749-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to indoor air pollution and the cognitive functioning of elderly rural women: a cross-sectional study using LASI data, India

Abstract: Background The majority of people in rural developing counties still rely on unclean and solid fuels for cooking, putting their health at risk. Adult and elderly women are most vulnerable due to prolonged exposure in cooking areas, and Indoor Air Pollution (IAP) may negatively impact their health and cognitive function. This study examines the effect of IAP on the cognitive function of middle-aged and elderly rural women in India. Methods The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Finally, our study is limited to the more conventional measures of SES. A worthwhile undertaking for future research would be to broaden the measurement of SES, to include environmental disadvantages (e.g., air pollution) and neighborhood adversities (e.g., disproportionate instances of covid-19 pandemic), in gauging social-structural inequities in cognitive health [ [100] , [101] , [102] ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study is limited to the more conventional measures of SES. A worthwhile undertaking for future research would be to broaden the measurement of SES, to include environmental disadvantages (e.g., air pollution) and neighborhood adversities (e.g., disproportionate instances of covid-19 pandemic), in gauging social-structural inequities in cognitive health [ [100] , [101] , [102] ].…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to the elderly (92) who tend to be less active in any case. It has been proven that staying in enclosed spaces for extended periods of time can have a drastic impact on both physical and mental health (93,94,95,96,97,98). Insomnia, increased levels of aggression, irritability, lowered immunological defences of the body, increased vulnerability to circulatory, respiratory, and metabolic diseases, as well as a deterioration of social life are only some of the problems modern societies face.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals showed that exposure to biodiesel fuels changed the expression of genes related to antioxidant defense and inflammation [8], which can cause falls [9]. Besides, the study found an increase in glial-fibrillary acidic protein (GFAP) in the corpus callosum of mice exposed to diesel particulate material [10], and long-term exposure to air pollution impaired cognitive function [11][12][13]. In human studies, it was found that healthy individuals exposed to high levels of air pollutants showed ultrafine particles in the olfactory bulb and αprominent nuclear proteins in neurons and glial cells, causing a decline in cognitive function [14].…”
Section: Introductionmentioning
confidence: 98%